Emotion Regulation and Self-Harm Among Forensic Psychiatric Patients - Laporte, Natalie; Klein Tuente, Stéphanie; Ozolins, Andrejs; Westrin, Åsa; Westling, Sofie; Wallinius, Märta (Frontiers in Psychology, 2021)
Emotion regulation has been specifically linked to both non-suicidal self-injury and attempted suicide. It is also known that self-harm is disproportionally higher (30%–68.4%) in forensic samples than in the general population, yet knowledge about the association between emotion regulation and self-harm in forensic settings is scarce. The purpose of this study was to describe emotion regulation in a sample of forensic psychiatric patients, to explore dimensions and levels of emotion regulation between forensic psychiatric patients with and without self-harm, and to explore associations between forensic psychiatric patients’ self-reported emotion regulation and self-reported functions of non-suicidal self-injury. A cohort of forensic psychiatric inpatients (N = 98) was consecutively recruited during 2016–2020 from a high-security forensic psychiatric clinic in Sweden. Data were collected through the self-report measures Difficulties in Emotion Regulation Scale (DERS) and Inventory of Statements About Self-injury (ISAS). In relation to the first aim, median total and subscales scores for DERS were reported. Results showed a statistically significant difference in emotion regulation between participants with and without self-harm (p = 0.004), with a medium effect size (Cohen’s d = 0.65) for the DERS total scale. The DERS subscales returned large differences for Impulse (p = .001, d = .86), Goals (p = .014, d = .58), and Strategies (p = .012, d = .54) between participants with and without self-harm. Finally, DERS scores were correlated to both the interpersonal (rs = .531, p < .001, n = 43) and intrapersonal factors (rs = .503, p < .001, n = 43) of non-suicidal self-injury as reported on the ISAS. Participants with self-harm (non-suicidal self-injury and/or suicide attempts) demonstrated significantly more difficulties with emotion regulation than those without self-harm. Emotion dysregulation was associated with both interpersonal and intrapersonal functions of non-suicidal self-injury in the participants. We suggest further studies on forensic psychiatric patients’ maladaptive behaviors that focus on substance abuse, self-harm, and aggressive behaviors in relation to the regulation and expression of emotion.